2022
DOI: 10.3390/d14050362
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Occurrence of Two Planktonic Ciliate Species (Urotricha, Prostomatida) Originating from High Mountain Lakes

Abstract: Ciliates of the genus Urotricha are widely distributed and occur in almost any freshwater body. Thus far, almost all species have been described from morphology only. Here, we applied an integrative approach on the morphology, molecular phylogeny and biogeography of two species isolated from high mountain lakes in the Central Alps, Austria. As these remote lakes are known to have water temperatures <15 °C, our hypothesis was that these urotrichs might prefer ‘cold’ environments. We studied the morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…indicated that the genus-specific probe likely covered most members of this genus in Lake Zurich. One reason for this encouraging finding are the recently published 18S rRNA gene sequences of five Urotricha species ( Frantal et al, 2022 ; Sonntag et al, 2022 ), that were included in the design of probe Uro-all-651. At the same time, the poor agreement between QPS and CARD-FISH in the sample from April 8, 2020 indicates that not all Urotricha species found in Lake Zurich may be covered by the probe.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…indicated that the genus-specific probe likely covered most members of this genus in Lake Zurich. One reason for this encouraging finding are the recently published 18S rRNA gene sequences of five Urotricha species ( Frantal et al, 2022 ; Sonntag et al, 2022 ), that were included in the design of probe Uro-all-651. At the same time, the poor agreement between QPS and CARD-FISH in the sample from April 8, 2020 indicates that not all Urotricha species found in Lake Zurich may be covered by the probe.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CARD-FISH could be a powerful tool for studying the in situ food preferences of, e.g., the omnivorous genus Urotricha . Representatives of this genus are widespread and abundant inhabitants of freshwater environments ( Müller, 1989 ; Posch et al, 2015 ; Šimek et al, 2019 ; Frantal et al, 2022 ; Sonntag et al, 2022 ), but little is known about their feeding strategies in situ ( Müller et al, 1991b ; Sonntag et al, 2006 ; Qu et al, 2021 ). In addition to food selectivity, CARD-FISH also provides the potential to further examine the symbiotic relationships within eukaryotic and between eukaryotic and prokaryotic microbes ( Chambouvet et al, 2008 ; Dirren and Posch, 2016 ; Lepère et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most prostomateans have only cursory original descriptions based exclusively on observations of live cells, with most of these occurring well before the molecular era (Carey 1992 ; Dragesco 1960 ; Kahl 1930 ). Only a handful of species have benefited from descriptions using modern techniques (Foissner 2021 ; Frantal et al 2022 ; Jiang et al 2021b , 2022 ; Sonntag et al 2022 ). There are also some ultrastructural studies of this group, which revealed details of several important characteristics such as the brosse and the extrusomes (Bardele 1999 ; Hiller 1991 , 1992 , 1993 ; Hiller and Bardele 1988 ; Lipscomb and Riordan 2012 ).…”
Section: Introductionmentioning
confidence: 99%